Normal values for high‐resolution anorectal manometry/topography in a healthy Korean population and the effects of gender and body mass index. Issue 4 (6th January 2014) - Lee, H. J.; Jung, K. W.; Han, S.; Kim, J. W.; Park, S.‐K.; Yoon, I. J.; Koo, H. S.; Seo, S. Y.; Yang, D.‐H.; Kim, K.‐J.; Ye, B. D.; Byeon, J.‐S.; et al.
Abstract Background High‐resolution manometry (HRM) based on spatiotemporal plots is increasingly being used. The aim this study was to evaluate, for the first time, the influence of gender, with adjustment for age, body mass index (BMI), and vaginal delivery, on anorectal functions in asymptomatic adults. Methods Fifty‐four asymptomatic healthy subjects (M : F = 27 : 27; age = 20–67 years) who were matched by age and gender were enrolled prospectively. We evaluated anorectal pressures, rectal sensation using a HRM probe, and balloon expulsion time. Multivariate linear regression analysis was performed to identify the independent effects of each factor. Key Results Anal resting pressure (median [IQR]; 32 [18] vs 46 [17] mmHg, p < 0.001), anal squeeze pressure (75 [28] vs 178 [72] mmHg, p < 0.001), rectal pressure (33 [16] vs 53 [46] mmHg, p = 0.009) and anal pressure (16 [17] vs 30 [36] mmHg, p = 0.019) during simulated evacuation with rectal distention, and the threshold for the desire to defecate (60 [20] vs 80 [60] mL, p = 0.020) were significantly lower in women than in men. BMI was positively correlated with anal resting pressure (95% CI: 0.598–2.947) and negatively correlated with the threshold for first sensation (95% CI: −0.099 to −0.015). Vaginal delivery did not affect any of the anorectal HRM parameters. Conclusions & Inferences HRM parameters may be associated with gender and BMI. Therefore, gender and BMI should be taken into consideration when interpreting HRM results.